Ethical Standards of Artificial Intelligence from the Perspective of Islamic Economics - Lataifeh, Amjad Salem; Abu Hija, Elias Abdullah (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to shed light on the ethical standards of Artificial Intelligence (AI) from an Islamic economic perspective. The subject is addressed through three main sections: the first defines the concepts of ethics and AI, the second outlines the ethical standards related to AI technologies, and the third provides an Islamic economic evaluation of these standards. Methods: The researchers employed a descriptive method to examine texts related to AI ethical standards in terms of their essence, forms, and classifications. Additionally, an analytical approach was used to extract the key Islamic ethical standards applicable to AI technologies and explore how these technologies can be harnessed to serve the economy and society while remaining consistent with Islamic values and principles. Results: The study finds that AI is a field of science focused on developing intelligent machines and software capable of performing tasks traditionally carried out by humans. The Islamic legal ruling on AI technologies depends on their appearance and intended use. If developed for impermissible purposes, they are deemed unlawful. However, if used for purposes that benefit individuals and the Muslim community - such as education, healthcare, or sustainable development - they are considered permissible. This permissibility is conditional upon the application of ethical standards, including humanity, inclusivity and justice, privacy and transparency, and responsibility and accountability. Conclusion: The scientific contribution of this study lies in its emphasis on the importance of aligning AI technologies with Islamic ethical standards. It highlights a consensus among Muslim scholars on the need to employ AI in ways that benefit the Islamic nation, promote justice, and serve human dignity without violating rights or core Islamic values.